2002
DOI: 10.1007/s00432-002-0374-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of von Hippel-Lindau gene mutation and methylation status on expression of transmembrane carbonic anhydrases in renal cell carcinoma

Abstract: These findings indicate that VHL suppresses CA IX expression but has no conclusive effect on CA XII and XIV expressions in RCC. CA IX expression is also driven by the methylation status of the CA9 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…Interestingly, aberrant methylation of CAIX has been demonstrated in renal cell carcinoma. [48][49][50] Supporting this, we also found indirect evidence for CAIX epigenetic regulation in this study with the re-expression of CAIX protein in the OVCA432 and UPN251 following chromatin modifying treatment with TSA.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, aberrant methylation of CAIX has been demonstrated in renal cell carcinoma. [48][49][50] Supporting this, we also found indirect evidence for CAIX epigenetic regulation in this study with the re-expression of CAIX protein in the OVCA432 and UPN251 following chromatin modifying treatment with TSA.…”
Section: Discussionsupporting
confidence: 81%
“…This finding explained overexpression of CA IX/CA XII in RCC. Further studies confirmed, at least for CA IX, that VHL mutations significantly correlate with CA9 expression in a series of RCC lines and that CA IX can identify early lesions in VHL kidneys [45,46] . Both CA IX and CA XII are subjected to pVHL control through HIF degradation also in normoxic tumor cells other than RCC and are induced in response to experimental as well as microenvironmental hypoxia [14,17] .…”
Section: Discussionmentioning
confidence: 87%
“…The studies from which the data has been extracted (refs. 6-34) have all been checked to ensure that data published in multiple reports are not duplicated with some publications omitted for this reason (1,35,(48)(49)(50). Gene and protein locations have been renumbered where necessary according to GenBank sequence: AF010238 for genomic VHL and L15409 for mRNA, with A of the first initiator ATG being 1 and codon numbers in accordance with L15409.…”
Section: Discussionmentioning
confidence: 99%